Аналіз алгоритмів побудови прихованих каналів на базі текстового контенту - Твердохліб, В. В.; Будянський, В. С. (ХНУРЕ, 2023)
Today, algorithms for constructing hidden channels, which are based on the use of text-type media, can compete with algorithms that, in turn, focus on the use of video, graphic and audio containers. Yes, today an extremely large number of, for example, web documents and accompanying files are transmitted over the network every second. These are, first of all, php, html, css, and external script files of various formats. Under such conditions, it makes sense to consider text steganography as one of the rather powerful tools for building hidden channels of data exchange.
Keywords: hidden channel; algorithm; text-type media; html; css; steganography